Exploring Needs of Health Educators on Education of Health Behaviors to Students: A Qualitative Study - Babak Nemat-Shahrbabaki; Arezoo Fallahi (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: The health educators, who are responsible health education in school, play a crucial role in the physical and mental health of students. The aim of this study was to explore the needs of health educators on education of health behaviors of students. Material and Methods: This qualitative study was conducted at the schools in Sanandaj city, located in the west of Iran, in 2016. Using purposive sampling, sixteen school health trainers with health education experience was included in the study. Data were collected through individual interview and group discussion, observation and fild notes, and analyzed by conventional content analysis. To confim the accuracy and strength of the data, acceptability, confimability and transferability components were taken into account. Results: Five categories and eighteen subcategories emerged from the data analysis, including strengthening organizational factors (intersectoral cooperation and external, monitoring of school health matters and solve the economic problems of schools), effiient manpower (use of appropriate human resources, improve the performance of trainers, strengthening communication skills of trainer and activate student health volunteers program), educational preparation (appropriate educational condition, advantage of the educational facilities, methods and models of teaching, pay attention to learnerʼs characteristics and design the educational content), attention to health of learner and trainer (pay attention to physical health of learner, pay attention to mental health of learner, pay attention to physical health of trainer and pay attention to mental health of trainer) and strengthening the role of family (improving cooperation of parents with school and Parental attention to learner). Conclusion: To deliver effiient and effective health education to students, health educators need to the inter-sectoral and extra-sectoral collaboration, giving more attention to the health promotion programs on the part of the authorities, equipping schools to educational equipment and facilities, and training educators.